Introduction to Soil Science - Anderson, Amber (Open textbook library., 2023)
This textbook introduces readers to the basics of soil science, including the physical, chemical, and biological properties of soils; soil formation, classification, and global distribution; soil health, soils and humanity, and sustainable land management.